Distribution of Tm3+ and Ni2+ in chalcogenide glass ceramics containing Ga2S3 nanocrystals: Influence on photoluminescence properties. Issue 7 (July 2019) - Lu, Xiaosong; Lai, Zhiqiang; Ren, Jing; Strizik, Lukas; Wagner, Tomas; Du, Yanqiu; Farrell, Gerald; Wang, Pengfei
Abstract: The distribution of Tm 3+ and Ni 2+ ions is unambiguously exhibited in 80GeS2 -20Ga2 S3 chalcogenide glass ceramics (GCs) containing Ga2 S3 nanocrystals (NCs) by using advanced analytical transmission electron microscopy. Distinctively different distribution patterns of Tm 3+ and Ni 2+ ions are observed in the GCs obtained by controlled crystallization. The distribution of the dopants imposes strong influence on their optical properties which are revealed by absorption and photoluminescence (PL) spectra. Detailed discussions are given of the mechanisms of the crystallization-induced PL enhancement and quenching of the Tm 3+ mid-infrared and Ni 2+ near-infrared emissions, respectively.